Domestic load, dependent care and home violence during the COVID-19 lockdown - Bardales-Mendoza, Olga (2023)
The Covid-19 pandemic carried Peru to confront many challenges in the public health system; we wonder about relationships at home during the quarantine period; even more when Peru has the challenge to reach de gender equality and decrease violence. Objective. To describe the distribution of the housework, dependent care and violence in home during the quarantine, according to gender. Methods: This is a descriptive study where a virtual questionnaire was applied to an intentional sample of 1,124 males and females above 18 years of age from all over Peru between May and July 2020. Results: Although most of the respondents indicated that they had shared housework during the lockdown, females assumed more frequently these labors alone than males, difference that was statistically significant. Both, males and females accepted that home violence increased during the lockdown, but the difference did not reach statistical significance. Conclusions: During the lockdown both males and females shared homework, but females assumed more responsibilities than males, home violence was perceived increasing.